(untitled) (Vietnam Journal of Community Medicine, 2025)
The objective of the study is to describe the current situation and some factors related to hepatitis C virus infection in patients receiving methadone treatment at the methadone treatment facility - Ha Long City Medical Center. Cross-sectional descriptive study on 384 patients treated with Methadone in Ha Long city. The rate of patients ever infected with hepatitis C virus before opioid addiction replacement treatment with methadone was 77.9%. Research results show that the group of patients with a high rate of HCV infection is related to the following factors: education level, duration of Metahdone treatment, having ever shared a needle, and ever having sex with a woman. The difference is statistically significant, with p < 0.05. People with high HCV infection rates have no difference with the following factors: marital status, HIV status and condom use. last sexual intercourse.